The Representation of Sexual Violence and Women's Resistance in the Novel Obsessive Loves by Shireishou - Jarmini Jarmini; Wiyatmi Wiyatmi; Anwar Efendi; Hartono Hartono (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the representation of sexual violence and women's resistance in Shireishou's novel Obsessive Loves. Utilizing a qualitative approach with content analysis, the research examines how the narrative addresses the psychological trauma of the victims and the patriarchal social structures that perpetuate sexual violence. Drawing on Freudian and Lacanian psychoanalytic theories alongside Walby’s feminist perspectives and the concept of rape culture, the study identifies and interprets critical excerpts from the novel. The findings reveal that Obsessive Loves portrays sexual violence as a systemic issue tied to power dynamics within patriarchal structures, reflecting deep psychological impacts such as PTSD and dissociation. The novel also highlights women's resistance as a form of empowerment and recovery, emphasizing the importance of solidarity and social support. This research contributes to feminist literary studies by demonstrating how fiction serves as a powerful medium for critiquing patriarchal norms and advocating for social change.